2009
DOI: 10.1016/j.solmat.2008.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Structural defects caused by a rough substrate and their influence on the performance of hydrogenated nano-crystalline silicon n–i–p solar cells

Abstract: a b s t r a c tWe present a cross-sectional transmission electron microscopy study of a set of hydrogenated nanocrystalline silicon n-i-p solar cells deposited by hot-wire chemical vapour deposition on Corning glass substrates coated with ZnO-covered Ag layers with various surface roughnesses. Strip-like structural defects (voids and low-density areas) are observed in the silicon layers originating from micro-valleys of Ag grains. A correlation between the opening angles of the textured surface and the appeara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
89
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(93 citation statements)
references
References 14 publications
3
89
0
Order By: Relevance
“…1f). Despite the reduced RMS roughness of these high water/DEZ ratio morphologies, it is believed that the surface features are sharper leading to higher defect density and therefore to lower FF and V oc values [14].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1f). Despite the reduced RMS roughness of these high water/DEZ ratio morphologies, it is believed that the surface features are sharper leading to higher defect density and therefore to lower FF and V oc values [14].…”
Section: Resultsmentioning
confidence: 99%
“…In order to fill this gap, we base our understanding on previous work showing that the morphology observed at the surface of LP-MOCVD ZnO results from a combination of both nucleation-and kinetic-driven phenomena [8][9][10][11][12][13][14][15][16][17]. In fact, it was demonstrated that temperature induced inter-facet diffusion could lead to the selection of different crystallographic PO [8].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that high aspect ratio features, while valuable for an optical improvement, are usually detrimental to the electrical performance of the solar cells, as they can easily induce the formation of low-density faulty regions [2,38,39]; a trade-off between optical and electrical properties must thus be found. valuable for an optical improvement, are usually detrimental to the electrical performance of the solar cells, as they can easily induce the formation of low-density faulty regions [2,38,39]; a trade-off between optical and electrical properties must thus be found. A post-growth refinement of the nanostructured glass morphology for improved electrical performance has been attempted via ion beam sputtering at normal incidence (normal-IBS), prior to solar cell deposition.…”
Section: Photon Harvesting In Thin Film Solar Cellsmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12][13][14][15] However, most of the time, a rough surface induces structural defects in the device grown on top of it, leading to reduced opencircuit voltage (V oc ) and fill factor (FF). 12,[14][15][16][17][18] Therefore, a compromise between roughness for efficient light scattering (high J sc ) and smoothness for high V oc and FF has to be made. A different approach is to decouple the growth interface from the scattering interface.…”
Section: Introductionmentioning
confidence: 99%